The Role of Body Image in Internalizing Mental Health Problems in Spanish Adolescents: An Analysis According to Sex, Age, and Socioeconomic Status - Ramos, Pilar; Moreno-Maldonado, Concepción; Moreno, Carmen; Rivera, Francisco (Frontiers in Psychology, 2019)
During adolescence there is a relatively high prevalence of weight problems and eating disorders. Furthermore, body image plays an important role in weight control and eating behaviors as well as in mental health. This study analyzes the influence of body mass index, perception of being overweight, and body image satisfaction on internalizing symptoms related to mental health in adolescents. In addition, sex, age, socioeconomic status, dieting, and physical activity are taken into consideration. This research is based on the international study Health Behaviour in School-aged Children (HBSC). The sample consists of 4531 Spanish adolescents from 13 to 18 years old. Participants were selected through random multi-stage sampling stratified by conglomerates. Two instruments were employed: the HBSC questionnaire and the Youth Self-Report (Achenbach System of Empirically Based Assessment, ASEBA). Results demonstrated that body image satisfaction –the emotional component related to body image– was the main predictor of adolescent internalizing symptoms. In addition, results show double-inequalities according to the interaction effects of sex, age, and socioeconomic status. Likewise, interesting results are shown regarding how dieting behaviors to lose or gain weight/volume and physical activity relate to body image perception and satisfaction, as well as with internalizing symptoms. This study highlights important body image aspects relevant to intervention and prevention of internalized mental health problems in adolescence.